Regional correlations in the development of rural economy - Káposzta, József (Studia Mundi – Economica, 2016)
In the 90s, the production structure in the rural economy underwent significant restructuring due to the change of regime, the changes in the land ownership, in the market economy as well as the transformed external economic and market relations. Based on such processes, the disparities between developed and areas lagging behind further increased. Obviously, the rural and spatial development policies, influencing such changes, are also under changes. In order to understand such restructurings and to achieve development, we must understand several spatial correlations. Overall, spatial differences and specializations both determine the major correlations of location selection in the Hungarian rural areas. All these factors together reflect the real spatial structure of today’s Hungarian rural areas, including the corporate and national economic interests, the potential improvement in efficiency considering small and large size units, as well as the increase in the quality of rural life.